Rice landscape management for raising water productivity, conserving resources, and improving livelihoods, in upper catchments of the Mekong and Red River basins - Pandey, S.; Bhandari, Humnath (CGIAR Challenge Program on Water and Food, 2010)
The project validated and disseminated a large number of improved rice-based cropping systems technologies suited to upland agro-ecologies. These improved technologies have good potentials to raise the productivity of water, land, and labor. The innovative strategies employed by the project including the paradigm of landscape management, multi-institutional partnership, multidisciplinary teamwork, farmer participatory approach to technology validation, and community-based seed production led to successful generation and dissemination of technologies. Initial monitoring to adoption of technologies showed good indications of spread and promising impacts on food security, poverty reduction, and environmental protection.